2003
DOI: 10.1007/s00421-002-0747-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnitopuncture on sympathetic and parasympathetic nerve activities in healthy drivers – assessment by power spectrum analysis of heart rate variability

Abstract: The object of this study was to assess the effects of magnitopuncture applied to Dazhui (DU14) point and Neiguan (PC6) points on sympathetic and parasympathetic nerve activities by power spectrum analysis of heart rate variability in healthy drivers during simulated driving. Using power spectrum analysis, the low frequency (LF) and high frequency (HF) components of heart rate variability can be calculated reflecting the sympathetic and parasympathetic activity. The 40 healthy male subjects were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 23 publications
(21 reference statements)
7
52
0
Order By: Relevance
“…The results indicated that the sympathovagal balance of healthy drivers under vibration conditions had changed significantly, while no similar significant change was obtained in the subjects under no vibration conditions in the same time session. The results have been proved for our previous study (Li, 2003) and supported by Gohara et al (1996). Considering crossover effects of time and vibration factor, we observed significant crossover effects in HF and LF:HF and no significant crossover effect in LF during simulated driving.…”
Section: Experimental Periodsupporting
confidence: 81%
“…The results indicated that the sympathovagal balance of healthy drivers under vibration conditions had changed significantly, while no similar significant change was obtained in the subjects under no vibration conditions in the same time session. The results have been proved for our previous study (Li, 2003) and supported by Gohara et al (1996). Considering crossover effects of time and vibration factor, we observed significant crossover effects in HF and LF:HF and no significant crossover effect in LF during simulated driving.…”
Section: Experimental Periodsupporting
confidence: 81%
“…Fatigue is believed to be a major contributing factor to errors made by drivers (Nilsson et al 1997). Our previous studies demonstrated that fatigue contributed to the decline of performance during prolonged driving (Li et al 2003(Li et al , 2004(Li et al , 2005. However, fatigue is a complex phenomenon that is not fully understood and is generally attributed to either central (neuronal) or peripheral (muscular) origin, or both (Gandevia 2001).…”
Section: Introductionmentioning
confidence: 94%
“…These evidences indicated that driving mental fatigue was induced after 90 min driving task. According to Li's subjective fatigue scale (LSFS) [24] (the subjective scores ranged from 1 to 7, a scale which represented no, minimally, somewhat, a little, considerably, very and extremely), the mental fatigue scores increased from 1.31 to 5.46 (P<0.005) at the end of task.…”
Section: Self-reportmentioning
confidence: 99%